Language change progress or decay? - Aitchison, Jean 1938- (Cambridge approaches to linguistics, 1991)
This book attempts to answer such questions by giving a lucid and up-to-date overview of language change. Why do people sometimes leave off the ends of words when they speak? Is it sloppiness, progress, or inevitable erosion? This book attempts to answer such questions by giving a lucid and up-to-date overview of language change. It discusses where our evidence about language change comes from, how and why changes happen, and how and why languages begin and end. It considers not only changes which occurred many years ago, but also those currently in progress. It does this within the framework of one central question - is language change a symptom of progress or decay?